A Rare Case of Spontaneous Remission and Relapse of a Primary Central Nervous System Lymphoma - Ramos, Rui (2018)
Primary central nervous system lymphoma remission after steroid treatment is a well-known phenomenon, but remission without any type of treatment is extremely rare. We present a rare case of spontaneous remission of a diffuse large B-cell lymphoma of the central nervous system as well as its subsequent reappearance in another location. The atypical presentation misled the neurosurgeons and neurologists, delaying diagnosis and treatment. The patient underwent brain biopsy after the relapse and started radiotherapy and chemotherapy with cytarabine + methotrexate + rituximab. As of 32 months after the diagnosis, the patient remained asymptomatic, with no focal neurological deficits and the disease in complete remission. A PubMed search of the literature up to June 2017 regarding spontaneous remission central nervous system lymphoma was also carried out.